Marketing: An Emerging Area - Sherrill Carlson (Journal of Applied Communications, 1990)
Communications professionals in the land-grant system are becoming more heavily involved in nonprofit marketing. A holistic client-centered approach to integrating program and communication efforts to advance the goals of the organization.